2009
DOI: 10.1345/aph.1l709
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sodium Bicarbonate–Induced Alkalemia in Cardiopulmonary Arrest Patients

Abstract: Administration of SB during CPA was causally linked with inducing alkalemia in 16% of patients. Early collection of ABG samples may assist in optimizing pH during CPA and thus reduce unwarranted empiric use of SB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Use of sodium bicarbonate during resuscitation of cardiac arrest is controversial. 16 We currently however do not use sodium bicarbonate injection or infusion as earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Use of sodium bicarbonate during resuscitation of cardiac arrest is controversial. 16 We currently however do not use sodium bicarbonate injection or infusion as earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral SB administration has known adverse effects, including hypokalemia, hypocalcemia, hyperosmolarity, and metabolic alkalosis, any one of which may induce life-threatening consequences (5)(6)(7). Increases in arterial pH also shift the oxyhemoglobin dissociation curve to the left, causing hemoglobin to bind oxygen more tightly (8).…”
mentioning
confidence: 99%
“…In patients where ABG data were available, bicarbonate administration was linked to alkalemia in 16% (10 of 61) of patients. The authors suggested that early ABG analysis in cardiac arrest may help optimize pH and reduce the frequency of empiric, not warranted, bicarbonate use [ 18 ].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Although patients who received bicarbonate had higher percentage of ROSC, regression analysis showed that bicarbonate administration did not significantly improve the rate of ROSC in out-of-hospital cardiac arrest [ 21 ]. The findings of all the above clinical studies are summarized in Table 1 [ 4 , 9-12 , 15 , 16 , 18 , 21-28 ]. Studies in the table are listed in alphabetical order based on the first author’s last name.…”
Section: Literature Search Resultsmentioning
confidence: 99%